2011
DOI: 10.1161/circresaha.111.243790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis - and trans -Acting Genetic Variants Explaining Up to Half the Variation in Circulating Vascular Endothelial Growth Factor Levels

Abstract: Rationale VEGF impacts angiogenesis, atherosclerosis and cancer. Although the heritability of circulating VEGF levels is high, little is known about its genetic underpinnings. Objective Our aim was to identify genetic variants associated with circulating VEGF levels using an unbiased genome-wide approach and explore their functional significance with gene expression and pathway analysis. Methods and results We undertook a genome-wide association study (GWAS) of serum VEGF levels in 3,527 participants of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(108 citation statements)
references
References 48 publications
13
92
2
1
Order By: Relevance
“…Therefore, it could regulate the expression of surrounding genes, including VEGFA . In a recent GWAS, we showed that the minor allele of rs6921438 strongly contributed to decreased VEGFA circulating levels (with an explained variance of VEGFA levels of 41%) ( 25 ). Subsequently, it appears that rs6921438 could have a negative effect in the cardiovascular system through a decrease in HDL-C levels, an increase in LDL-C levels, and a decrease in VEGFA levels.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, it could regulate the expression of surrounding genes, including VEGFA . In a recent GWAS, we showed that the minor allele of rs6921438 strongly contributed to decreased VEGFA circulating levels (with an explained variance of VEGFA levels of 41%) ( 25 ). Subsequently, it appears that rs6921438 could have a negative effect in the cardiovascular system through a decrease in HDL-C levels, an increase in LDL-C levels, and a decrease in VEGFA levels.…”
Section: Resultsmentioning
confidence: 91%
“…Also, rs6921438 has not been identifi ed in any previous GWAS concerning HDL-C and LDL-C levels (34)(35)(36)(37)(38)(39)(40)(41)(42)(43). The existing GWASs have managed to explain a small percentage of the blood lipid trait variance (e.g., for HDL-C, it ranges from 0.6% to 10%); thus, Supplemental Material can be found at: ( 23,25 ). Finally, Sandhofer et al ( 24 ) have shown that plasma VEGFA levels were negatively associated with TC and LDL-C in a healthy female sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The challenge is further compounded by the presence of large linkage disequilibrium across large segments on the chromosomes, as well as the trans effects of other variants or chromosomal regions. 65,66 Furthermore, as stated earlier, the ENCODE findings suggest the presence of a large number of regulatory and putatively functional genomic regions, 21 which poses additional challenge in the selection of candidate genes and single nucleotide polymorphisms for functional characterizations. An additional layer of complexity is the inadequateness of in vitro models and model organisms in accurately reflecting the functional significance of the variants in humans.…”
Section: The Editors Recent Developments In Cardiovascular Genetics E89mentioning
confidence: 74%